Ingrid goes West - Spicer, Matt; Plaza, Aubrey, 1984-; Olsen, Elizabeth, 1989-; Ice Cube, (Musician) Jr., 1991- (Universal City, CA : Universal Pictures Home Entertainment, 2017)
Following the death of her mother, a young girl moves to Los Angeles to befriend a social media star.
Originally released as a motion picture in 2017.
Dolby digital 5.1, wide screen 2.40:1.
Features: deleted scenes; director's commentary.
Aubrey Plaza, Elizabeth Olsen, O'Shea Jackson Jr., Wyatt Russell, Billy Magnussen.
MPAA rating: R.
This is a Blu-ray disc which can only be played on Blu-ray disc players and will not play on standard DVD players.
Keywords: Socialites -- Drama; Social media -- Drama; Female friendship -- Drama; Los Angeles (Calif.) -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Comedy films